Pelatihan Pembuatan Raised Bed dari Barang Bekas dengan Metode Hugelkultur Bagi Masyarakat di Desa Karang Jaya - Ria Dwi Jayati; Eka Lokaria; Linna Fitriani; Sepriyaningsih Sepriyaningsih (LP4MK STKIP PGRI Lubuklinggau, 2025)
This community service program aims to provide training to the Karang Jaya Village community on making raised beds using used goods with the Hugelkultur method, in order to improve environmentally friendly and sustainable farming skills. The training was carried out through a participatory approach, where the community was directly involved in every stage of the activity. The program began with a theoretical explanation of the Hugelkultur technique, followed by a demonstration of making raised beds using used goods found around the residents' homes, then conducting direct practice of making raised beds with the Hugelkultur Technique in the field to deepen their understanding. This program succeeded in increasing participants' understanding of the concept of sustainable agriculture and waste management into useful materials for agriculture. The participants showed high enthusiasm and were able to make raised beds with the Hugelkultur technique independently, and were able to utilize used goods around their environment to optimize agricultural yields. This community service program succeeded in providing significant benefits to the Karang Jaya Village community in developing environmentally friendly farming skills. The Hugelkultur method taught can improve the sustainability of household agriculture with more efficient and environmentally friendly costs.